Heritage routes and multiple narratives. The Inca Road System (Qhapaq Ñan, Camino principal andino / Andean road system): a specific case of a non-tourism heritage route? - Elodie Salin (Via@)
This article discusses the heritage producing machine where transnational cultural routes are concerned, and specifically in the light of the heritage narratives established at different scales by those involved in heritage development. It comprises a heuristic reflection on the notion of heritage and on the quest for inscription on the UNESCO World Heritage List through the categories of cultural landscapes and heritage routes. The study of the Qhapaq Ñan (Camino principal andino / Andean road system), some 4,000 km of roads across six Andean countries from Colombia in the north to Argentina and Chile in the south, inscribed on the World Heritage List in 2014, provides a geopolitical interpretation of an ambitious transnational cultural project. The issue of sharing the values embodied by the heritage route are examined through multiple narratives, glorifying a remembrance that, while shared, yet lacks consensus. The tourism development (ecotourism) of the Qhapaq Ñan is expected, rejected and conflictual, as are the multiple narratives that punctuate the Inca Road System and the difficult appropriations of this fragmented heritage route.